Towards sustainable conservation science in cultural heritage: bridging the gap between contemporary conservation theory and the philosophy of science in approaches to authenticity questions - Markevicius, Tomas; Olsson, Nina (Frontiers in Materials, 2023)
As contemporary artists' practices evolve to incorporate ever-newer forms and approaches, conservators are encountering challenges not met before, that influence the development of sustainable and green treatment methods and materials. Many challenges stem from how we understand and articulate authenticity and cultural heritage. In approaching authenticity, the conservation field seeks to rely on reliable knowledge, supplied by science that has been playing an ever more critical role in conservation and technical art history. While conservation science techniques are relatively well-known to conservators, the foundational ethos of the scientific inquiry that distinguishes science from other intellectual pursuits needs to be clarified. Exploration of the foundational ethos of science and the philosophy of science has lacked in conservation, which creates communication problems for stakeholders with different backgrounds: curators, conservators, art historians, and scientists, who operate in different realms, but need to produce knowledge across disciplines and collectively. To bridge this knowledge gap in authenticity questions, the authors take the perspective of the philosophy of science and discuss what makes the scientific inquiry distinct from other intellectual pursuits in the context of conservation. As a workable solution for cultural heritage, the authors propose adopting a concept of scientific attitude as a science demarcation criterion, introduced by Lee McIntyre. The new demarcation criterion, based on values rather than methodology, offers a sustainable approach to defining the role of present-day science in cultural heritage and building sustainable connections with diverse frameworks of knowledge used in conservation and authenticity questions.